2018
DOI: 10.2135/cropsci2018.04.0261
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Additive and Dominance Effects on Agronomical and Nutritional Traits, and Multivariate Selection on Urochloa spp. Hybrids

Abstract: A tropical forage breeding program contains several peculiarities, especially when it involves polyploid species and facultative apomixis. Urochloa spp. are excellent perennial forages, and the identification of superior genotypes depends on the selection of many characteristics under complex genetic control, with high cost and time‐consuming evaluation. Therefore, the use of tools such as multivariate analysis and diallel analyses could contribute to improving the efficiency of breeding programs. Thus, the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 46 publications
8
30
2
Order By: Relevance
“…This may indicate that both selection methods allowed accumulation of favorable alleles with partial or complete dominance in one selection cycle. These results are similar to those reported before in P. notatum (Marcón et al., 2019) and in Brachiaria (Matias et al., 2018), where heterosis was mainly due to dominance genetic effects, which may be supporting the hypothesis that in apomictic species, hybrid vigor is due to the accumulation of favorable, dominant alleles rather than to interallelic interactions.…”
Section: Discussionsupporting
confidence: 92%
“…This may indicate that both selection methods allowed accumulation of favorable alleles with partial or complete dominance in one selection cycle. These results are similar to those reported before in P. notatum (Marcón et al., 2019) and in Brachiaria (Matias et al., 2018), where heterosis was mainly due to dominance genetic effects, which may be supporting the hypothesis that in apomictic species, hybrid vigor is due to the accumulation of favorable, dominant alleles rather than to interallelic interactions.…”
Section: Discussionsupporting
confidence: 92%
“…This scenario shows the predominance of variance caused by additive effects in the absence of epitasis (Falconer and Mackay, ; Ramalho et al, ). In a diallel with Urochloa species ( U. ruziziensis , U. decumbens and U. brizantha ), the predominance of additive or dominance effects changed regarding agronomic and nutritional trait assessed (Matias et al ). The traits density of regrown tillers, regrowth speed, LDM, CP, NDF and IVDMO were predominantly additive, with proportions varying from 20% to 90%, whereas LIG showed only dominance effect of 53%.…”
Section: Discussionmentioning
confidence: 99%
“…There are some examples of diallel use in allopolyploids such as Urochloa spp. (Matias et al, ), wheat ( Triticum aestivum L.; Gowda, Friedrich, Longin, Lein, & Reif, ) and in autopolyploids such as alfalfa ( Medicago sativa L.; Groose, Kojis, & Bingham, ; Masood et al, ) and potato ( Solanum tuberosum L.; Menezes, Pinto, & Lambert, ). In the study of Matias et al () involving three species of Urochloa genus ( U. ruziziensis (syn.…”
Section: Introductionmentioning
confidence: 99%
“…Cuts 1, 4, 5, and 6 were performed in the wet season, whereas Cuts 2, 3, and 7 in the dry season. The full experimental design and biological materials (hybrids and checks) were previously described by Matias et al (2018). This population was at the breeding stage highlighted at Fig.…”
Section: Plant Materials and Phenotypingmentioning
confidence: 99%
“…The cloud of points for both ploidies had a triangular shape, but with a different orientation. The genomic structure from the original diallelic cross of this population (Matias et al, 2018) can be identified by the PCA using diploid or tetraploid data configuration.…”
Section: Gene Annotationmentioning
confidence: 99%